Viabilitas Polen Aren pada Media Buatan - DONATA S. PANDIN; ELSJE T. TENDA (Pusat Penelitian dan Pengembangan Perkebunan, 2010)
Sugarpalm Pollen Viability on Artificial MediaResearch conducted at the Plant Breeding Laboratory of Indonesia Coconut and Other Palmae Research Institute (ICOPRI) Manado, from February until April 2010. The research aims to find ways of processing sugarpalm pollen and testing techniques of pollen viability. The materials used were male flowers of the Tall type of sugarpalm. Pollen viability test carried out using a completely randomized design with 12 treatments of 2, 4, 6, 8, 10, 12, 14, 16, 18, 20, 22, 24 hours after sown on growth media, and repeated three times. The results showed that the sugarpalm male flower drying good for the process of pollen is to use an oven or a dehumidifier at a temperature of 35 o C - 37 o C for 30 hours. The yield of sugarpalm pollen produced an average of 1.41%. The results showed that pollen viability of sugarpalm not germinated until 12 hours after sowing, and just started to sprout after 14 hours with the percentage increasing until 24 hours after grown. Sugarpalm highest pollen viability was found on treatment after 24 hours of observation.